Habitat selection in Many-colored Rush Tyrant (Tachuris rubrigastra) and Wren-like Rushbird (Phleocryptes melanops) in the subtropical salt marshes of Brazil - Favretto, Mario Arthur; Machado-de-Souza, Tiago; Golec, Cláudia; Reinert, Bianca Luiza; Bornschein, Marcos Ricardo [UNESP] (Taylor & Francis, 2022)
The Many-colored Rush Tyrant (Tachuris rubrigastra) and Wren-like Rushbird (Phleocryptes melanops) are birds that inhabit the subtropical salt marshes of Brazil, a newly recognized ecosystem of tidal marshes. We studied the habitat selection of these species in the subtropical salt marshes, characterizing the vegetation types where the species did and did not occur in the same habitats. The species occurred in a total of four very simplified vegetation types, characterized by the dominance of one or two plant species, including Schoenoplectus californicus, Crinum americanum, Cladium jamaicense, and Typha domingensis. We found that the habitats selected by the birds have very specific phytophysiognomic characteristics related to vegetation height and density. Moreover, the lower altitudes of certain areas of occurrence implies longer and higher flooding during periods of high tides; thus, the greater height of the vegetation maintains an above-water-level foraging and protective area for the birds. The fact that subtropical salt marshes are a transitional ecosystem suggests the possibility of rapid changes in plant succession or an intensification of the tropicalization process with mangrove expansion, which could eliminate habitat characteristics that are crucial to the survival of these two bird species in the subtropical salt marshes of Brazil.
Keywords: Climate change; conservation; estuaries; phytosociology; pioneer formations